2012
DOI: 10.1038/cr.2012.58
|View full text |Cite
|
Sign up to set email alerts
|

K48-linked ubiquitination and protein degradation regulate 53BP1 recruitment at DNA damage sites

Abstract: Efficient DNA damage sensing and repair is crucial to preserve genomic integrity and failure to detect or repair DNA breaks can cause mutations, contributing to the formation of tumors. One key protein required for mediating DNA repair is the tumor suppressor 53BP1. Recent studies now demonstrate the crucial role of K48-linked ubiquitination and protein degradation for 53BP1 recruitment at sites of DNA damage.The linking of ubiquitin chains to proteins is a multistep process involving three different types of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(26 citation statements)
references
References 17 publications
0
25
1
Order By: Relevance
“…This result indicated that proteasome inhibition 30 minutes prior to DNA damage did not abrogate tight binding of 53BP1 to damage sites in chromatin. While prior studies had suggested that the RNF8-mediated degradation of KDM4A/JMJD2A was required to expose H4K20me2 for the recruitment of 53BP1 to DNA damage sites [16] , [23] , [24] , our result revealed that the block due to KDM4A/JMJD2A binding to the chromatin was not absolute, and 53BP1 could still bind to the damage sites. We conclude from Figure 7C that proteasome inhibition by MG132 does not abolish 53BP1 association with IRIF, but blocks the degradation of the unbound bulk 53BP1, accounting for the failure to recruit RIF1 to the damage sites.…”
Section: Resultscontrasting
confidence: 83%
“…This result indicated that proteasome inhibition 30 minutes prior to DNA damage did not abrogate tight binding of 53BP1 to damage sites in chromatin. While prior studies had suggested that the RNF8-mediated degradation of KDM4A/JMJD2A was required to expose H4K20me2 for the recruitment of 53BP1 to DNA damage sites [16] , [23] , [24] , our result revealed that the block due to KDM4A/JMJD2A binding to the chromatin was not absolute, and 53BP1 could still bind to the damage sites. We conclude from Figure 7C that proteasome inhibition by MG132 does not abolish 53BP1 association with IRIF, but blocks the degradation of the unbound bulk 53BP1, accounting for the failure to recruit RIF1 to the damage sites.…”
Section: Resultscontrasting
confidence: 83%
“…Finally, because K63-linked ubiquitination is a docking site for mediating protein-protein interactions or conformational changes (55), we examined whether METTL3 could regulate this ubiquitin-linked chain of 3D. HEK293T cells, in which METTL3 was overexpressed or knocked down, were expressed with Flag-3D and HA-K63, followed by IP and immunobloting.…”
Section: Resultsmentioning
confidence: 99%
“…The E3 ubiquitin ligase RNF168 is required for the recruitment of 53BP1 to sites of DNA double-strand breaks ( Doil et al, 2009 ; Mallette et al, 2012 ; Mallette and Richard, 2012 ). We created RNF168 knockout Plk4 AS cells and confirmed that although 53BP1 is present at normal levels in these cells, it fails to localize to sites of DNA damage ( Fig.…”
Section: Resultsmentioning
confidence: 99%